The Prostate Health Index (PHI) Density: Are There Advantages Over PHI or Over the Prostate-Specific Antigen Density? - Garrido, M (2021)
Background and aims: Overdiagnosis of prostate cancer (PCa) should be minimized. We wanted to evaluate the diagnostic performance of the prostate health index density (PHID) and compare it with that of the prostate health index (PHI) alone and of the prostate-specific antigen density (PSAD). Materials and methods: 232 men scheduled for a prostate biopsy (prostate-specific antigen level: 2-10 µg/L), were enrolled. PHI, PHID and PSAD were evaluated considering PCa and clinically significant PCa (csPCa) as the outcomes. Results: For PCa, the area under the curve (AUC) was higher for PHID (0.823) than for PHI (0.779) and PSAD (0.776). For csPCa, the AUC was also higher for PHID (0.851) but closer to that of PSAD (0.819) and PHI (0.813). For equal sensitivities (90%) for PCa, PHID and PSAD offered the highest specificities (37%), missing the same number of cancers (n = 11). Considering csPCa, PHI and PHID had similar specificities. PSAD reached the highest specificity (50.0%), sparing 32.8% of biopsies, while missing 9 cases of csPCa. Conclusions: PHID has a better diagnostic performance than PHI for overall PCa detection, but very close to the PSAD performance. Considering csPCa, PHI and PHID perform almost equally, but PSAD has a better diagnostic performance.